Demographic Characteristics and Prevalence of Mandibular Condylar Fractures at a Tertiary Care Dental Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2017)
Background: Mandibular condylar fracture is a critical condition. Objectives: The purpose of the study was to see the demographic characteristics and prevalence of mandibular condylar fractures. Methodology: This cross-sectional study was conducted in the Department of Oral and Maxillofacial Surgery of Dhaka Dental College and Hospital from January 2009 to September 2010 for a period of one year and nine months. All the patients presented with mandibular condylar fractures at any age with both sexes were included as study population. Details demographic characteristics and the rate of occurrence were recorded. Result: A total number of 26 patients were included in this study. Majority of the patients were male (88.5%) and age belongs to 21 to 30 years (38.5%). Road traffic accident (46.2%) was the main cause and unilateral fractures were more frequent. The prevalence of mandibular condylar fracture was 14.9%. Conclusion: Mandibular condylar fracture is most commonly occurred in male with a low prevalence.Journal of National Institute of Neurosciences Bangladesh, 2015;1(2): 50-52